2020
DOI: 10.24191/ajue.v16i1.8991
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Teachers' Implementation and Strategies on Higher Order Thinking Skills in School Based Assessment Instruments

Abstract: Higher Order Thinking Skills (HOTS) among students is crucial to be developed in the education system as to prepare students to face the 21st century situations as well as to develop students to reach their full potential. In Malaysia, the integration of HOTS in the new School Based Assessment is a move towards realizing the government's aspiration of achieving a quality education system. The study seeks to investigate teachers' challenges and their strategies on integrating Higher Order Thinking Skills (HOTS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 6 publications
4
39
0
1
Order By: Relevance
“…The Malaysia Education Blueprint 2013-2025 was launched to ensure that the Malaysian education system remained relevant, vibrantly attractive and effective (Nusrah & Chan, 2020;Tai & Omar, 2018;Wilson & Narasuman, 2020). While school reforms have targeted the improvement of learning achievements of students, research has indicated that there is a significant link between PLCs and the improvement in teachers' practice (Voelkel & Chrispeels, 2017;Zhang & Sun, 2019;Cansoy & Parlar, 2017) and student achievement (Lomos, Hofman, & Bosker, 2011;Ozdemir, 2019;Huggins, Scheurich and Morgan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Malaysia Education Blueprint 2013-2025 was launched to ensure that the Malaysian education system remained relevant, vibrantly attractive and effective (Nusrah & Chan, 2020;Tai & Omar, 2018;Wilson & Narasuman, 2020). While school reforms have targeted the improvement of learning achievements of students, research has indicated that there is a significant link between PLCs and the improvement in teachers' practice (Voelkel & Chrispeels, 2017;Zhang & Sun, 2019;Cansoy & Parlar, 2017) and student achievement (Lomos, Hofman, & Bosker, 2011;Ozdemir, 2019;Huggins, Scheurich and Morgan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…From this research, an instrument with appropriate indicators was obtained to assess the high level of thinking ability in the material of the circulatory system. The impact of the existence of this instrument for teachers is that it can be used as a means of training learners to familiarize themselves with thinking at a high level and become a collection of quality questions (Utama et al, 2020), for learners can be used to know and train high-level thinking skills (Kholis et al, 2020) and for schools this instrument can be useful to familiarize learners using high-level thinking skills so as to improve the quality of learners (Arifin, 2018;Wilson & Narasuman, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A set of questionnaires was used to collect information regarding the supervisors' supervisory styles as perceived by counselling interns and counselling interns' satisfaction during the supervision process. The study was conducted using a descriptive quantitative design which adopts a survey design (Wilson & Narasuman, 2020). The styles are based on the Adaptive Supervision in Counselor Training (ASiCT) Model by Rando.…”
Section: Instrumentsmentioning
confidence: 99%